Phenotyping women with detrusor underactivity by presumed etiology: Is it plausible?. Issue 4 (26th July 2016) - Brown, Elizabeth T.; Cohn, Joshua A.; Kaufman, Melissa R.; Dmochowski, Roger R.; Reynolds, William S.
Abstract : Aims: Underactive bladder (UAB) is a symptom complex with poorly characterized causation. The aim of this study was to determine if clinical and UDS parameters differed between categories of presumed detrusor underactivity (DU) etiologies. Methods: A retrospective review was performed at a single institution from 2011 to 2015 to identify patients with symptoms of UAB. Patients were excluded if they were male, had anti‐incontinence, or pelvic organ prolapse (POP) surgery within 1 year, or the UDS did not demonstrate DU as defined within. Subjects were stratified by etiology into four cohorts: cardiovascular disease manifestations (CV), cardiac risk factors (CVR), neurologic (N), or idiopathic (I). Patient demographics, comorbidities, symptomatology, physical exam, and UDS parameters were compared. Results: A total of 200 patients met inclusion criteria (CV: n = 53 [26.5%], CVR: n = 44 [22%] N: n = 81 [40.5%], I: n = 22 [11%]). Women in the CV cohort were significantly older and more likely to be post‐menopausal ( P  < 0.001). There were no differences between cohorts for BMI ( P  = 0.48), recurrent UTI ( P  = 0.63), history of urinary retention (AUR) ( P  = 0.65), POP (0.49), American Urological Association Symptom Score (AUA‐SS) ( P  = 0.06), presenting symptomatology [urgency, frequency, urgency urinary incontinence, AUR, incomplete emptying, hesitancy, UTI ( P  = 0.97)], or UDS parameters (first sensation [ P  = 0.25], normal desire [ P  = 0.80], strong desire [ P  = 0.58], capacity [ P  = 0.11], Qmax [ P  = 0.50], Pdet at Qmax [ P  = 0.22], post‐void residual [ P  = 0.82]). Conclusions: Though differences were observed between cohorts for age and menopausal status, clinical or urodynamic parameters did not demonstrate distinct differences across presumed categories of etiology, suggesting that the etiology of DU may be multifactorial. Neurourol. Urodynam. 36:1151–1154, 2017 . © 2016 Wiley Periodicals, Inc.